Encouraging Political Voices of Underrepresented Citizens through Coproduction: Evidence from a Randomized Field Trial. Issue 3 (5th June 2018) - Hjortskov, Morten; Andersen, Simon Calmar; Jakobsen, Morten
Abstract: Not all citizens' voices are heard with equal strength in the political chorus. Based on studies of policy feedback, we suggest that engaging underrepresented citizens in the production of public services (i.e., making them "coproducers") increases their political voice. We use a field experiment to test the effect of involving ethnic minorities in the education of their children on their propensity to directly voice their preferences with the education policy through government citizen surveys and their tendency to vote in elections. Among these normally underrepresented citizens, coproduction increased their propensity to voice their preferences to politicians through citizen surveys but not their tendency to vote. The effect on voicing in government citizen surveys tends to be larger among nonvoters. The results indicate how policies involving underrepresented citizens can raise the voices of people who would not otherwise be heard.